Hydraulic Behavior in The Downflow Hanging Sponge Bioreactor - Machdar, Izarul (Jurnal Litbang Industri, 2016)
Performance efficiency in a Downflow Hanging Sponge (DHS) bioreactor is associated with the amount of time that a wastewater remains in the bioreactor. The bioreactor is considered as a plug flow reactor and its hydraulic residence time (HRT) depends on the void volume of packing material and the flow rate. In this study, hydraulic behavior of DHS bioreactor was investigated by using tracer method. Two types of sponge module covers, cylindrical plastic frame (module-1) and plastic hair roller (module-2), were investigated and compared. A concentrated NaCl solution used as an inert tracer and input as a pulse at the inlet of DHS bioreactor. Analysis of the residence time distribution (RTD) curves provided interpretation of the index distribution or holdup water (active volume), the degree of short-circuiting, number of tanks in series (the plug flow characteristic), and the dispersion number. It was found that the actual HRT was primarily shorter than theoretical HRT of each test. Holdup water of the DHS bioreactor ranged from 60% to 97% and 36% to 60% of module-1 and module-2, respectively. Eventhough module-1 has higher effective volume than module-2, result showed that the dispersion numbers of the two modules were not significant difference. Furthermore, N-values were found larger at a higher flow rate. It was concluded that a DHS bioreactor design should incorporated a combination of water distributor system, higher loading rate at startup process to generate a hydraulic behavior closer to an ideal plug flow.ABSTRAKEfisiensi unjuk kerja bioreactor Downflow Hanging Sponge (DHS) berkaitan dengan lamanya waktu tinggal limbah berada di dalam bioreaktor tersebut. Bioreaktor DHS dianggap sebagai seuatu reaktor aliran sumbat (plug flow) dimana waktu tinggal hidraulik (HRT) tergantung pada volume pori material isian dan laju alir. Dua jenis modul digunakan dalam penelitian ini, yang diberi nama dengan module-1 dan module-2 untuk melihat pengaruh jenis modul terhadap karakteristik hidraulik. Dalam eksperimen ini, nilai HRT diteliti menggunakan metode pencacahan (tracer). Hasil dari kurva residence time distribution (RTD) dianalisis nilai volume aktif, tingkat short-circuiting, karakteristik plug flow (jumlah seri tangki berpengaduk, N-value), dan bilangan dispersi. Dari hasil penelitian diperoleh HRT atual lebih singkat dari HRT teoritis. Volume aktif bioreaktor bernilai antara 60% sampai 90% dan 36% sampai 60% untuk masing-masing modul-1 dan modul-2. Walaupun volume efektif module-1 lebih besar dari modul-2, bilangan dispersi untuk kedua modul tidak berbeda secara signifikan. Nilai N-value diperoleh lebih besar pada laju alir lebih besar. Dari penelitian ini, maka dapat disimpulkan bahwa desain bioreaktor DHS sangat berhubungan dengan sistem distribusi limbah cair dan laju alir yang tinggi untuk mendapatkan kondisi bioreaktor mendekati sistem plug flow ideal.